Os índios do Brasil no pensamento de Carl Friedrich Philipp von Martius (1823-1844) - Silva, Seles Pereira da (2013)
Issues relating to indigenous peoples to Brazil, conceived as a nation, have gained great importance from the third decade of the nineteenth century. With the establishment of the Portuguese kingdom in their colonial domains in Americas in 1808, the old colonial structure collapsed, culminating in the events of 1822. But since the end of the first decade of the nineteenth century, the entering of many foreigners led to the production of many speeches that, with the founding of the new nation in the tropics, came to compose the debates about the identity of Brazil and the Brazilian. Many of these foreigners were associated with European scientific circles and - or - members of the nobility. Armed with the tools of modern science, as from the Illustration, spread from Europe, these men explored extensive and diverse regions. Their records show a wealth of details and interpretations of space and man of that period, and its analysis provides us with important clues for the understanding of various issues pertaining to Brazil. One of these travelers is the Bavarian Carl Friedrich Philipp von Martius, who together with Johann Baptist von Spix, arrived in 1817. Both made a trip of about three years, which resulted in extensive scientific and literary production. Besides the work Travel in Brazil, the Brazilian narrative of the journey written by von Martius co-authored with von Spix, which has been the main source of this research, von Martius published a number of other works, namely: The rule of law among native of Brazil (Munich, 1832), The Past and Future of American man (Freiburg, 1838) and the treaty How to Write the History of Brazil (Rio de Janeiro, 1844). Von Martius also wrote the novel Frey Apollonio, but this work was never published by the author and came to light only posthumously, in 1992. In Brazil, the publication and circulation of scientific writings had the support of the Brazilian Historical and Geographical Institute, founded in 1838. The hypothesis of this research is that, in the context of formation of Brazil as a nation, von Martius stands as one of the first authors that not only defines indigenous peoples as Brazilians - especially in his treaty of 1844 - but he fosters and develops a series of studies aimed to search for his story. Besides the narrative of the expedition, Travel in Brazil, the research uses the three aforementioned scientific writings and the romance Frey Apollonio. Based on these works, the survey covers a period of approximately 20 years of life and intellectual work of the Bavarian, between 1823 and 1844.